Vitamin D Status and Lung Function in Stable COPD: A Cross-Sectional Study - Lubis, Ayu Zulhafni (Community Medicine and Education Journal, 2024)
Chronic obstructive pulmonary disease (COPD) is a major global health concern characterized by progressive airflow limitation. Vitamin D deficiency has been linked to impaired lung function and increased inflammation, suggesting a potential role in COPD pathogenesis. This study aimed to investigate the relationship between vitamin D status and lung function in patients with stable COPD. A cross-sectional study was conducted involving 51 stable COPD patients. Spirometry was performed to assess lung function, and serum 25-hydroxyvitamin D [25(OH)D] levels were measured. The association between 25(OH)D levels and lung function parameters, including forced expiratory volume in one second (FEV1), was analyzed using Pearson correlation. The mean age of the participants was 64.05 ± 8.05 years, and all were male. The majority (47.1%) had severe airflow limitation (FEV1 < 30% predicted). The mean 25(OH)D level was 27.57 ± 6.74 ng/mL, indicating insufficiency in most patients. No significant correlation was found between 25(OH)D levels and FEV1 (r = -0.131, p = 0.180). In conclusion, this study did not find a significant association between vitamin D status and lung function in stable COPD patients. Further research, including longitudinal studies and interventional trials, is needed to elucidate the complex relationship between vitamin D and COPD and to determine the potential benefits of vitamin D supplementation in this population.